Investigation of the Radiographer’s adherence and compliance with radiation protection and infection control practices during COVID-19 mobile radiography - Khandaker, Mayeen Uddin *; Abuzaid, Mohamed M.; Mohamed, Ikhlas A.; Yousef, M.; Jastaniah, Saddig; Alshammari, Qurain T.; Alghamdi, Salem Saeed; Osman, Hamid; Ahmed, Amna Mohamed; Musa, Alamin; Medani, Afaf Mohamed Ahmed; Lam, S.E.; et al. (Elsevier, 2023)
Radiological staff, especially radiographers, work as front liners against the COVID-19 outbreak. This study aims to assess compliance with radiation protection and infection control practices during COVID-19 mobile radiography procedures. This cross-sectional study included 234 radiographers (females, 56%, n = 131; males, 44%, n = 103) who were asked to complete an online questionnaire consisting of demographic data, radiation protection and infection control practices during COVID-19 portable cases, and knowledge and awareness. After informed consent was completed, SPSS statistical software was used for the data analysis. The most common age group of participants ranged from 18 to 25 years old (30.3%, n = 71). Bachelor's degree holders were 74.4% (n = 174). Most radiographers (39.7%, n = 93) had a working experience of 1–5 years, followed by 27.8% (n = 65) with more than 16 years of experience. Most respondents (62.4%, n = 146) handled approximately 1–5 cases daily, the majority of them (56%, n = 131) stated affirmatively they had obtained special training to handle COVID-19, and when inquired if they had received any special allowances for handling COVID-19 suspected/confirmed cases most of them stated negative (73.9%, n = 173). Most participants stated that they always wear a TLD during portable cases (67.1%, n = 157) and a lead apron (51.7%, n = 121). Around 73% (n = 171) knew the latest information on COVID-19 and attended the COVID-19 awareness course. A significant association was found between the work experience of the radiographers and their responses to following the best practices (p = 0.018, α = 0.05). Radiographers who had COVID-19 training (μ = 48.78) tend to adhere more to best practices than those who have not (p = 0.04, α = 0.05). Further, respondents who handled more than 16/more COVID-19 suspected/confirmed cases followed the best practices more (μ = 50.38) than those who handled less (p = 0.04, α = 0.05). This study revealed detailed information on radiation protection and infection control practices during COVID-19 mobile radiography. It has been observed that the participants/radiographers have good knowledge and awareness of radiation protection and infection-control practices. The present results may be used to plan future requirements regarding resources and training to ensure patient safety.